Sign Communication and Health Monitoring system for Armed Forces - R.Kavitha, Durga Shree.S, Jeyanthan .G, (International Journal of Advanced Science and Technology, 2020)
In Battle fields soldiers are frequently injured because of lack of communication. Immediate medical assistance can enhance the life of the soldiers in case of injury. This project enables the soldiers to have proper communication; Guidance and it also prevent them from fatal injury. It also monitors the health parameters and provide   immediate medical assistance if necessary. This project improves the safety of the soldier by using a hand glove which continuously monitors the soldier heart beats per minute. The sensors and lily pad Arduino are embedded in the glove. The glove has PIR sensor which detects the presence of human around the soldier. With the help of PIR sensor the alert is given to the soldier when the human presence is there. If the pressure, heart beat of the soldier is reduced to certain limit, message is sent to the central control office via GSM. With the help of this communication, the commander can easily back up or make further decision to protect the soldiers. It also helps to track the injured soldier for medical assistance. To reduce the miscommunication sign communication is performed through hand gloves embedded with the flex sensor. The signals are sent via Bluetooth among the soldiers.